Pengaruh Model Pembelajaran SAVI (Somatic, Auditory, Visual, Intellectual) terhadap Kemampuan Pemahaman Konsep IPA Siswa Kelas 3 SDIT Kaifa - Azka Nazhia; Muhammad Fahri; Ikhwan Hamdani (FONDATIA, 2026)
The low understanding of science concepts among elementary school students needs attention, particularly in lower grades as the initial stage in the formation of conceptual understanding. This condition is related to the learning process, which still tends to focus on memorization and does not sufficiently involve meaningful learning experiences. This study aimed to determine the effect of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on the science concept understanding ability of third-grade students at SDIT Kaifa. This study used a quantitative approach with a quasi-experimental design. The research sample was selected using purposive sampling and consisted of 50 students from two classes, namely 25 students in the experimental group and 25 students in the control group. Data were collected through a concept understanding test in the form of a pretest and posttest, and then analyzed through normality testing, homogeneity testing, and hypothesis testing using an independent sample t-test. The results showed a significant difference between the control class and the experimental class, with a Sig. value of 0.000 < 0.05. This finding proves that the SAVI learning model has an effect on improving students’ understanding of science concepts. The conclusion of this study emphasizes that the SAVI model can serve as a more active and meaningful learning alternative that is appropriate to the characteristics of elementary school students in understanding science concepts. The implications of this study provide recommendations for teachers to apply the SAVI model in science learning and open opportunities for further research at different levels, materials, or learning contexts.